(untitled) (Journal of The Colloquium for Information Systems Security Education, 2023)
The University of Washington (UW) published their pedagogical model for Cybersecurity Education – the Kuzima-Bespalko-Popovsky (KBP) model. In 2005, the National Center for Academic Excellence in Cybersecurity certified the status of NCAE-CR based on the tight pairing to the Knowledge Units (KUs). The KBP model aided in maintaining the quality of the instruction. The original KBP model goals are reviewed here and the changes to those goals are explained. The model provided a solid public – private partnership engagement model. Industry professionals from the field taught the NIST / NICE KSAs and provided real-time experience, contributing to the curriculum’s resiliency. We modified our competency assessment from the World of Work Inventory (WOWI) assessment test to the CYBERGenius.IQ, integrated industry-based CERT material for scalability, and created a certified student collaboratory to manage continuing education post-graduation into the job.